MENJAGA IMUNITAS TUBUH MELALUI PROGRAM SENAM DALAM UPAYA PENCEGAHAN PENYEBARAN COVID-19 DI DESA SUKOREJO - Wasilatul bariroh; Nur Layla (Kalam Nusantara Institute, 2023)
Early childhood is a population that is experiencing a growth process that is very supportive in the future, most people do not pay attention to children's growth, both physical and spiritual growth, therefore the community needs to be fostered to carry out good immunity for children for a better nation's young generation in the future In times like now there is an epidemic, namely the covid-19 virus which has been evenly distributed among us, if young children are infected with the covid-19 virus then our hopes for Indonesia will be victorious in the future. The Indonesian population at any time experiences an increase in the covid-19 virus, therefore it is necessary to do prevention before being exposed to the covid-19 virus as implemented by Sukorejo Kotaanyar Paiton Probolinggo Village, especially at the Nurul Ulum foundation which has increased immunity through an exercise program in an effort to prevent the spread this covid-19 program is carried out at the Nurul Ulum foundation every morning at 07.00 WIB which is attended by all early childhood children to maintain a healthy lifestyle for early childhood. This article explores education for the community about adapting to new habits. PKM-based on activities are a form of community service by students with cross-scientific and sectoral approaches regarding forms of adapting to new habits as well as steps to improve the immune system, as well as analyzing factors related to participating in gymnastics in the area of ​​the Nurul Ulum foundation, Sukorejo Village, RT 01 Kotaanyar Paiton Probolinggo.